Patterns of care and treatment outcomes in patients age 80 or older with non-metastatic pancreatic cancer. Issue 4 (May 2020) - Li, Richard; Vazquez, Jessica; Novak, Jennifer; Sedrak, Mina; Warner, Susanne; Glaser, Scott; Chen, Yi-Jen; Dale, William; Amini, Arya
Abstract: Introduction: Older adults are underrepresented in landmark trials that determine treatment guidelines for pancreatic cancer. We used the National Cancer Database (NCDB) to compare treatment patterns and outcomes in stage I-III pancreatic cancer between older adult patients, defined as age 80 or older, to patients younger than 80. Material and Methods: We identified 140, 678 patients in the NCDB diagnosed with pancreatic cancer from 2004 to 2015. Patients with metastatic disease or non-adenocarcinoma histologies were excluded. Descriptive statistics comparing patients age 80+ and age <80 were generated. Logistic regression was used to evaluate predictors of cancer-directed therapy receipt (defined as receipt of chemotherapy, radiation, or surgery) in older patients, and Cox proportional hazards modeling was performed to evaluate survival in the older cohort. Results: We identified 140, 678 patients with non-metastatic pancreatic cancer, of which 23, 395 patients (16.6%) were 80 or older. Among older patients, 44.5% of patients received cancer-directed therapy compared to 78.7% among other patients ( p  < .001). Older patients had worse 2-year survival at 11.3% versus 27.5% for younger (p < .001). 2-year survivorship decreased further in older patients who received no cancer-directed treatment, at 4.7% compared with 19.5% for older patients receiving treatment ( p  < .001). After propensity score matching, cancer-directed treatment remained associated with improved survival for older patients (hazard ratio 0.42; 95% confidence interval 0.41–0.43; p  < .001). Discussion: Rates of cancer-directed therapy were low in patients age 80+, with 55.5% receiving no therapy. Cancer-directed treatment was associated with an overall survival benefit. Future trials are needed to define optimal treatment paradigms in this population.